Management of Land Owned by the Village Government for Improving Community Welfare: The Maqashid Syariah Approach - Renny Oktafia (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2022)
Tourism village was one of the factors that can move the economy of the village community. This study aims to determine the management of village land used as agro-tourism land, and its impact on improving the welfare of the people of Kebaron Village, Krembung District, Sidoarjo Regency. This research was qualitative method with a case study research approach. The result found that village land which was managed for guava picking agro-tourism by using lease transactions. The impact of this agro-tourism is that the community experiences an increase in welfare, because it provides a place for the community to work, increase community income, make village land productive and improve village facilities. To measure welfare, the maqashid sharia indicator is used, so that welfare is measured in 5 things, namely: Hifdz Ad-Din, Hifdz An-Nafs, Hifdz Al-Aql, Hifdz An-Nasl, Hifdz Al-Mal. This research was expected to contribute to the management of agro-tourism land and the welfare of tourism industries in indonesia.